تجلّيات الصوت والدلالة في المقطوعة النوفمبرية رقم 52 من إلياذة الجزائر لمفدي زكريا: دراسة تطبيقية للفونيمات التّطريزية - منقور, عبد الجليل (University of Eloued جامعة الوادي, 2023)
تهدف هذه الورقة البحثية إلى رصد وبيان القيمة المعنوية للصوت في تشكيل دلالات الشّعر، وذلك من خلال الأثر الدلالي للفونيمات التطريزية أو ما يعرف بالفونيمات فوق التركيبية. ومعلوم أنّ تلك الظواهر الصوتية تزيد التحاما بالمعنى والدلالة حين أدائها نطقا، نظرا لأهمية المنطوق وتأثيره الخاص ودوره في تقديم المعنى بشكل أوضح. ومنه جاء اختيارنا لتطبيق الظاهرة في المقطوعة النوفمبرية 52 من "إلياذة الجزائر" للشاعر الملحمي الجزائري مفدي زكريا. ومن خلال القراءة الوصفية التحليلية، والاستعانة باستخراج وإحصاء المقاطع الصوتية وتقديم دلالتها، خلصت الدراسة إلى أنّ المقاطع الصوتية في المقطوعة النوفمبرية لشاعر الثورة الجزائرية المجيدة مفدي زكريا جاءت متباينة، وكلّ مقطع منها يحمل بعدا دلاليا مختلفا، لذلك تناغمت في القصيدة المشاعر وتباينت بشكل واضح وصريح مع ما يختلج الشاعر من أحاسيس صادقة. Abstract: This paper aims to monitor and explain the intangible value of sound in forming the semantics of poetry, through the semantic effect of embroidered phonemes or what is known as suprastructural phonemes. It is known that these phonemic phenomena increase the bonding of the meaning and the significance when they are performed verbally, according to the importance of the utterance, its special influence, and its role in presenting the meaning more clearly. Hence our choice to apply the phenomenon in the November piece 52 of the "Iliad of Algeria" by the Algerian epic poet Mufdi Zakaria. Through the descriptive analytical reading, extracting and counting the phonemes, and presenting their significance, the study concluded that the phonemes in the November piece of the glorious Algerian revolution poet Mufdi Zakaria were different, and each of them carried a different semantic dimension, so the poem harmonized with feelings and contrasted clearly and explicitly with what Convulsed in the same poet of sincere feelings.
مقال